Mobile Interventional Stroke Teams Improve Outcomes in the Early Time Window for Large Vessel Occlusion Stroke. Issue 9 (September 2021) - Morey, Jacob R.; Zhang, Xiangnan; Marayati, Naoum Fares; Matsoukas, Stavros; Fiano, Emily; Oxley, Thomas; Dangayach, Neha; Stein, Laura K.; Fara, Michael G.; Skliut, Maryna; Kellner, Christopher; De Leacy, Reade; et al.
Abstract : Background and Purpose: Endovascular thrombectomy for large vessel occlusion stroke is a time-sensitive intervention. The use of a Mobile Interventional Stroke Team (MIST) traveling to Thrombectomy Capable Stroke Centers to perform endovascular thrombectomy has been shown to be significantly faster with improved discharge outcomes, as compared with the drip-and-ship (DS) model. The effect of the MIST model stratified by time of presentation has yet to be studied. We hypothesize that patients who present in the early window (last known well of ⩽6 hours) will have better clinical outcomes in the MIST model. Methods: The NYC MIST Trial and a prospectively collected stroke database were assessed for patients undergoing endovascular thrombectomy from January 2017 to February 2020. Patients presenting in early and late time windows were analyzed separately. The primary end point was the proportion with a good outcome (modified Rankin Scale score of 0–2) at 90 days. Secondary end points included discharge National Institutes of Health Stroke Scale and modified Rankin Scale. Results: Among 561 cases, 226 patients fit inclusion criteria and were categorized into MIST and DS cohorts. Exclusion criteria included a baseline modified Rankin Scale score of >2, inpatient status, or fluctuating exams. In the early window, 54% (40/74) had a good 90-day outcome in the MIST model, as compared with 28% (24/86) in the DS model ( P <0.01). In the late window, outcomes were similar (35% versus 41%; P =0.77). The median National Institutes of Health Stroke Scale at discharge was 5.0 and 12.0 in the early window ( P <0.01) and 5.0 and 11.0 in the late window ( P =0.11) in the MIST and DS models, respectively. The early window discharge modified Rankin Scale was significantly better in the MIST model ( P <0.01) and similar in the late window ( P =0.41). Conclusions: The MIST model in the early time window results in better 90-day outcomes compared with the DS model. This may be due to the MIST capturing high-risk fast progressors at an earlier time point. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03048292. Abstract : Supplemental Digital Content is available in the text.